Nutritional value of chips made from coconut residue flour - Reyes, Rafael Tayao; Galvez, Flor Crisanta F. (1995.)
The effects of amounts of coconut residue flour (CRF) and water in the formulation, and the fat content of CRF on the nutritional value of chips were studied in two phases. Ohase I involved the determination of the effects of varying levels o CRF (0%, 15%, 30%) and water (45%, 50%, 55%) on the moisture, fat, ash, protein, crude, fiber and available carbohydrate contents of chips. In Phase II, effect of varying levels of fat content of CRF (23%, 28%, 33%) and amount of CRF (20%, 35%, 50%) on these nutritional components were studied. A 3x3 full factorial design was employed in both phases. Results indicated no significant effect of amounts of CRF and water in the formulation on ash, protein and carbohydrate contents of the chips produced. Only the moisture, fat and crude fiber contents were affected. When fat content in CRF and amount of CRF were varied, there was significant difference in fat, ash and carbohydrate contents of chips. Other nutritional components such as moisture, protein and crude fiber were not affected.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Coconut residue flour; Coconut chips